Gambaran Peresepan Obat Untuk Pasien Asma Rawat Jalan di Klinik X Dumai - Muhajri Agusfina; Renatalia Fika; Ainun Naim; Annisa Juwita Dalimunthe (Journal Pharma Saintika, 2024)
Asthma is a heterogeneous disease with chronic inflammation of the airways involving inflammatory cells in them, which will respond excessively to a trigger, causing episodic symptoms such as wheezing, shortness of breath, a feeling of pressure in the chest, and coughing (especially in the morning and evening). The aim of this research is to determine the description of drug prescribing for asthma patients at the X Dumai Clinic. This research method was carried out using a retrospective method at the X Dumai Clinic Outpatient Pharmacy during the period July to December 2022. The instruments used were asthma patient prescription sheets and patient prescription data collection sheets. Sampling was carried out using the random sampling method. The number of samples that met the inclusion criteria for this study was 222 patients. Based on gender and age, from the results of research that has been carried out, it is found that the percentage (%) of drug use in asthma patients based on female gender is as high as 122 patients (54.95%) and 100 patients (45.05%) were male. Based on age, it showed that most patients were aged 56-65 years with 59 patients (26.58%). Based on the therapeutic pattern of drug classes, the active drug substance in the drug dosage form showed the highest percentage of 31.98%. Namely Salbutamol. Meanwhile, combination asthma drug prescriptions were 20.27%. Namely Salbutamol and Methylprednisolone.